2014
DOI: 10.1038/srep06568
|View full text |Cite
|
Sign up to set email alerts
|

Splash dispersal of Phyllosticta citricarpa conidia from infected citrus fruit

Abstract: Rain-splash dispersal of Phyllosticta citricarpa (syn. Guignardia citricarpa) conidia (pycnidiospores) from infected oranges was studied in still air and combined with wind. High power microscopy demonstrated the presence of conidia in splash droplets from diseased oranges, which exuded conidia for over one hour during repeated wetting. The largest (5 mm) incident drops produced the highest splashes (up to 41.0 cm). A linear-by-quadratic surface model predicted highest splashes to be 41.91 cm at a horizontal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…These infections, which also occur under nets because of their permeability, cause scab, a disease that generates dark spots on the fruit and reduces its commercial value 8 . Wind speed has an impact on drying time and propagation of infection 9 and a large mesh size for exclusion nets is preferred to allow wind to pass through easily.…”
mentioning
confidence: 99%
“…These infections, which also occur under nets because of their permeability, cause scab, a disease that generates dark spots on the fruit and reduces its commercial value 8 . Wind speed has an impact on drying time and propagation of infection 9 and a large mesh size for exclusion nets is preferred to allow wind to pass through easily.…”
mentioning
confidence: 99%
“…and reduced viability compared to the ascospore, however, recent work suggest that water and wind may disperse conidia over longer distances than previously reported 16 .…”
mentioning
confidence: 55%
“…The increase in severity on fruit on the swale side of the tree to equal that of the road side of the tree may indicate disease progression from road to swale and indicate the direction from which the inoculum spread. Indeed, it has been shown that wind driven splash droplets can propel conidia upwards and outwards from the point of origin and this distance increases under the influence of wind 16 . Clearly the ascospore is not required for the spread of the disease into the topmost sections of the canopy (>3 m).…”
Section: Discussionmentioning
confidence: 99%
“…Spores were suspended in 2 mL of sodium chloride aqueous solution (NaCl, 0.85 w/v) and removed from sporulating colonies with a sterile pipette. Suspensions were adjusted to 10 6 conidia/mL (similar to Perryman et al, 2014)).…”
Section: Fungal Inoculation Assaysmentioning
confidence: 99%